Nail involvement in Langerhans cell histiocytosis: Diagnostic and prognostic Clues - Sirait, Sondang P.; Rihatmadja, Rahadi; Prayogo, Rizky Lendl; Arisanty, Riesye; Melviana, Gisca; Ohara, Kuniaki (Journal of General - Procedural Dermatology and Venereology Indonesia, 2020)
Introduction: Despite its rarity, nail involvement in Langerhans cell histiocytosis (LCH) may show various clinical presentations. This study aims to show the roles of nail involvement in LCH patients as the diagnostic and prognostic clues.Case illustrations: We presented four cases of multisystem LCH in children which were already confirmed by skin biopsy with various nail abnormalities. We were able to perform nail biopsy in two patients and confirmed the nail involvement. Histopathological examination showed the infiltration of Langerhans cells characterized by indented/reniform nuclei and CD1a expressions. All patients had high-risk organ involvements. Discussion: Langerhans cells may infiltrate the nail bed, proximal nail fold, and nail matrix. Further infiltration may destruct the nail plate. Hypothetically, we suggest that the nail bed as the initial infiltration site of Langerhans cells. The different sites of involvement lead to different clinical presentation. Nail abnormalities may predict a poorer prognosis, as they mostly occur in patients with multisystem disease. Conclusions: Nails should be routinely inspected in the suspicion of LCH. The presence of nail abnormalities in LCH patients may predict a poorer prognosis.